Implementasi Model Project-Based Learning (PjBL) Berbasis Deep Learning untuk Meningkatkan Penguasaan Kosa Kata Bahasa Arab - Khairunnisa; Setiadi, Fadlan Masykura (Program Studi Pendidikan Bahasa Arab, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
This study aims to gain an in-depth understanding of the implementation process of the Project-Based Learning (PjBL) model integrated with Deep Learning to enhance Arabic vocabulary acquisition among elementary school students within the framework of the Merdeka Curriculum. A qualitative approach with a case study design was employed, focusing on exploring students’ learning experiences, teachers’ instructional strategies, and classroom interaction dynamics during the application of the model. The research was conducted at SD Islam Terpadu Al Furqon Madina, involving one Arabic language teacher and ten fifth-grade students as research participants. Data were collected through participatory observation, in-depth interviews, and documentation of students’ project outcomes. The findings reveal that implementing PjBL integrated with Deep Learning enhances students’ active engagement in Arabic vocabulary learning, strengthens conceptual understanding, and fosters deep thinking skills through collaborative and reflective activities. The teacher acts as a facilitator, guiding students toward meaningful learning supported by contextual learning media. These findings underscore the significance of project-based pedagogical innovation in enriching Arabic language learning experiences in elementary schools, aligning with the Merdeka Curriculum’s emphasis on active, collaborative, and contextual learning.